SYSTEMATIC LITERATURE REVIEW: LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS ETNOMATEMATIKA - Susanti, Octa Lilis; Yanto, Yufitri; Luthfiana, Maria (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2024)
The culture that develops in society can be used as material for learning mathematics. This scientific article was prepared using the Systematic Literature Review (SLR) method. SLR is a method for identifying, reviewing and concluding several studies related to the themes discussed. The articles studied were 18 articles related to the development of LKPD based on an ethnomathematics approach in mathematics learning, which came from the Google Schoolar database from 2015-2024. The results of the article review show that ethnomathematics is a study that can be applied to LKPD in mathematics learning. This is from research that ethnomathematics can improve students' abilities. Several cultural variations can be displayed in ethnomathematics, such as traditional games, building forms, traditional food, traditional houses and activities from traditional villages.